Empowering Coastal Women Entrepreneurship Groups in An Effort to Improve Prokelok (Local Wisdom Productivity) Based on Digital Entrepreneurship in Labuhan Haji Beach, East Lombok Regency: Pemberdayaan Kelompok Wanita Wirausaha Pesisir dalam Upaya Meningkatkan Prokelok (Produktivitas Kearifan Lokal) Berbasis Digital Entrepreneurship di Pantai Labuhan Haji Kabupaten Lombok Timur - Yuniar Bahri, Salmi; Chalel Rahman, Abdul; Hartiani, Hartiani; Jamil, Sultanil; Apriani Damayanti, Sri (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PKM) activity was conducted with the Coastal Women Entrepreneurs Joint Business Group (Kube) located on the coast of Labuhan Haji, East Lombok Regency, West Nusa Tenggara (NTB). Over the past two years, the partners' businesses have not shown significant growth due to limited knowledge and skills. This situation is evident in the partners' inability to create innovative products. The products sold by the partners are processed foods with short shelf life, resulting in low sales value. Furthermore, the partners faced challenges in product marketing, which was limited to their business premises, with a limited target audience of visitors/tourists. To address this issue, the Community Service (PKM) Team of the Muhammadiyah Selong Institute of Social and Health Technology (ITSKes) provided solutions in the form of workshops and mentoring on entrepreneurship, digital marketing using websites and social media (Facebook, Instagram, TikTok), and label design using the Canva app. In addition to the workshops, practical work on making fish floss and fish crackers was also conducted. The goal of these solutions was to create product diversity and expand product marketing. The impact of implementing technology and innovation for partners can transform conventional business activities into digital entrepreneurship, the process of managing a business using digital technology